Fantastic lizards and where to find them: cis-Andean microteiids (Squamata: Alopoglossidae & Gymnophthalmidae) from the Colombian Orinoquia and Amazonia - Diago-Toro, María F.; García-Cobos, Daniela; Brigante-Luna, Giovanni D.; Vásquez-Restrepo, Juan D. (Zootaxa, 2021)
Although Colombia is perceived as one of the most diverse countries in reptiles, the distribution of many microteiid lizards of the Alopoglossidae and Gymnophthalmidae families is still poorly known. This is particularly true for those species in the cis-Andean regions, in part due to the remoteness or socio-political issues within some of these territories. In order to elucidate the diversity and distribution of the cis-Andean microteiids in Colombia, in this study we present a review based on the examination of specimens deposited in the reptile collection at Instituto de Investigación Alexander von Humboldt, one of the most important Colombian biological collections, and data from the literature. We reported a total of 29 taxa, in which three are new records for Colombia and three are range extensions. Two species were assigned to species complex because their morphological determination was non-conclusive, and three were identified just to genus, since they may correspond to more than one entity or be currently non-described. We found that nine species are distributed in both the Amazonia and Orinoquia regions, nine are currently only present in the Amazonia and seven are in the Orinoquia. Based on our data, we highlight the importance of using local museums to increase the taxonomic and geographic data coverage, we discuss the taxonomic difficulties for some taxa, as well as the potential for future research and their constraints. Finally, we present a taxonomic key for the identification of the microteiids present in the Orinoquia and Amazonia regions of Colombia.